2007
DOI: 10.1007/s10585-007-9119-1
|View full text |Cite
|
Sign up to set email alerts
|

Rho GTPases: functions and association with cancer

Abstract: Rho GTPases are small proteins that act as binary molecular switches in a wide range of signalling pathways upon stimulation of cell surface receptors. Three different classes of regulatory proteins control their activity. In the activated state small GTPases are able to bind a variety of effector proteins and initiate downstream signalling. Rho GTPases regulate important cellular processes ranging from cytoskeletal remodelling and gene expression to cell proliferation and membrane trafficking. Therefore it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
210
0
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(217 citation statements)
references
References 157 publications
0
210
0
7
Order By: Relevance
“…Because of the lack of evidence regarding Rac1 mutations in human cancers, deregulated Rac1 activity is closely associated with the elevated expression or aberrant activation of Rac1-associated guanine nucleotide exchange factors (GEFs). 27 Thus, FAK may activate Rac1 in OSCC cells by phosphorylating Rac1-associated GEFs. This notion is supported by the observations that Tiam1 and Vav2, two Rac1-associated GEFs, can be phosphorylated by c-Src and, in turn, leads to Rac1 activation and cell invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the lack of evidence regarding Rac1 mutations in human cancers, deregulated Rac1 activity is closely associated with the elevated expression or aberrant activation of Rac1-associated guanine nucleotide exchange factors (GEFs). 27 Thus, FAK may activate Rac1 in OSCC cells by phosphorylating Rac1-associated GEFs. This notion is supported by the observations that Tiam1 and Vav2, two Rac1-associated GEFs, can be phosphorylated by c-Src and, in turn, leads to Rac1 activation and cell invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Mammary acini are hollow samples when compared with the low or undetectable expression detected in normal tissue samples. 6,[12][13][14] In vitro and in vivo studies have shown important roles for Cdc42 in regulating diverse cellular processes such as cell cycle progression and mitosis, polarity, survival, differentiation and stem cell function. Increasing evidence suggests that Cdc42 may play distinct roles in different cell and tissue types, and whether Cdc42 is crucial during normal MEC morphogenesis remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Therefore, Rho GTPase signaling has been involved in many aspects of cancer biology, from tumor initiation to tumor cell proliferation, invasion and metastasis. 6,7 How Rho GTPases are modulated in tumor is currently a major and a challenging issue. Most studies have monitored the expression levels of Rho GTPases in human cancer and several of them have been found overexpressed.…”
mentioning
confidence: 99%